Introductory Guide to Agent-Based Simulation Development on the GAMA Platform - Santos, Aline Rodrigues; Santos, Fernando (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2024: Anais do XVIII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2024.33459, 2024)
The use of agent-based simulations is becoming common in the research field, being employed to abstract complex concepts through visual demonstrations. This has driven the emergence of platforms for developing these simulations. In this context, GAMA stands out as a good option due to its wide range of features. However, GAMA still lacks materials to guide beginner developers. With the aim of filling this gap, this paper presents an introductory guide to simulation development in GAMA. The paper describes the main functionalities and the structure for developing a simulation in GAMA. Beside that, the paper exemplifies these elements through the development of the ’Sugarscape’ simulation, known in the community. Finally, the challenges that a beginner developer may encounter are reported, along with recommendations to address them.